Gender Statactivism and NGOs: Development and Use of Gender Sensitive-Data for Mobilizations and Women’s Rights - De Rosa, Eugenia (PARTECIPAZIONE E CONFLITTO, 2014)
Historically, NGOs and civil society organizations have engaged actively in the development of new forms of gender categorizations, gender-sensitive data and gender analysis, mainly within a human rights framework. But, what is the actual space for NGOs to promote mobilization on women’s rights and, more specifically, how do NGOs develop and use gender-sensitive data for social mobilizations? Mainly based on the study of 5 worldwide NGOs and 3 networks of human rights experts, operating at different levels, the paper investigates the different ways these organizations intervene in gender issues, focusing on how they strategically produce and use categorizations and data. An initial typology is presented by analyzing «gender statactivism» of NGOs. Four phases of mobilization are identified: (a) knowledge and framing processes, (b) policy analysis, policy design and policy implementation, (c) action (campaigning and advocacy) and (d) monitoring and evaluation. The paper concludes by discussing potentiality, controversies and issues related to gender statactivism by NGOs, and stresses implications for the debate on the Post-2015 Development agenda and the potentiality for integrating «gender statactivism» into a framework of particularly transnational intersectionality